Угода про припинення зобов’язання переданням відступного: зміст та особливі ознаки - Рассказова, В. В.; Rasskazova, V. V. (Вісник Харківського національного університету внутрішніх справ. – 2023. – № 2 (101), ч. 1. - С. 43-51, 2023)
Зазначено, що у забезпеченні стабільного правозастосування важливе значення мають правильне трактування функцій інституту відступного та єдині підходи до реалізації механізму укладення і виконання угоди про передання відступного. Стаття є оригінальною науковою роботою, в якій досліджено правову природу правочину щодо передання відступного, його особливі властивості та значення в конструкції припинення зобов’язання відступним. Наголошено на функції угоди про відступне – зафіксувати досягнення домовленості сторін на припинення основного зобов’язання саме в такий спосіб, а також обґрунтовано цю особливість угоди про передання відступного як поєднання ознак правовстановлюючого та правоприпиняючого юридичного факту. Обґрунтовано думку, що саме зміст угоди між кредитором і боржником про передання відступного, яка укладена з дотриманням вимог чинного законодавства, дозволяє відмежувати відступне від суміжних інститутів зобов’язального права, визначити природу правовідносин між сторонами, якщо виникають спірні ситуації.

In order to ensure stable law enforcement, it is important to have a correct interpretation of the functions of the institution of indemnity and unified approaches to the implementation of the mechanism for concluding and executing an agreement on the transfer of indemnity. The legal nature of the transfer of indemnity, its special properties and significance in the construction of termination of an obligation by indemnity have been investigated. It has been emphasized that the function of the indemnity agreement is to record the parties’ agreement to terminate the principal obligation in this way, as well as explained the peculiarity of the indemnity agreement as a combination of the features of the law-establishing and law-terminating legal fact, since the agreement both gives rise to additional rights and obligations for the parties and serves to terminate the original obligation as a result of its execution i.e. transfer of the indemnity by the debtor to the creditor. It has been suggested that it is the content of the agreement between the creditor and the debtor on the transfer of the indemnity, which is concluded in compliance with the requirements of current legislation, that allows distinguishing the indemnity from related institutions of law of obligations, and determining the nature of legal relations between the parties in case of disputes. For example, debt forgiveness is a law-terminating legal fact presented in the form of a transaction that does not create an obligation between the creditor and the debtor, and novation, unlike indemnity, does not provide for the termination of the binding relationship between the parties, but rather the preservation of such a relationship in a modified form. Attention has also been drawn to the inadmissibility of entering into an agreement on indemnity by third parties who are not parties to the original obligation. Thus, the mechanism of termination of an obligation by indemnity is based solely on the will of the parties and their mutual agreement on all essential terms of indemnity transfer, which excludes any form of participation of a third party in the decision to terminate the obligation between the creditor and the debtor in this way.

Исследована правовая природа сделки по передаче отступного, его особые свойства и значение в конструкции прекращения обязательства отступным. Отмечено функции соглашения об отступном – зафиксировать достижение договоренности сторон на прекращение основного обязательства именно таким способом, а также обоснована эта особенность соглашения о передаче отступного как сочетание признаков правоустанавливающего и прекращающего юридического факта.
Agreement on the termination of obligation by transferring indemnity: content and special features
Keywords: відступне; угода; припинення цивільного зобов’язання; передання предмета відступного; indemnity; agreement; termination of a civil obligation; transfer of the subject of indemnity; отступное; соглашение; прекращение гражданского обязательства; передача предмета отступного